The Transatlantic Narco-Nexus: - Rodrigues, Thiago (2023)
The article analyzes the contemporary transatlantic flow ofillegal drugs, taking on account the current transformationof the connections among South American, African andEuropean Drug-Trafficking Organizations (ODTs) and thetendency to securitize this traffic which interests the Brazilianpublic, national and regional security and diplomatic policies.The article presents a history of the transatlantic drug-trafficking and the its contemporary contours in order tosuggest viable initiatives to cope with this new and aggravatedpanorama pushed through by the so-called “war on drugs”.